BLUE GIANTS BETWEEN L330 AND L35 - IRIARTE ERRO, B; CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1955)
227 stars have been classified as supergiants. All these stars are near the galactic equator and between l=330° and l=35°.
BOL OBS TONAN TACUB
Keywords: BLUE, GIANTS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS